2015
DOI: 10.5152/tjar.2014.66934
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Desflurane and Propofol on the Release of Thyroid Hormones in Euthyroid Patients Undergoing Elective Lumbar Discectomy

Abstract: Amaç: Bu çalışmanın amacı tek seviye lomber diskektomi ameliyatı geçiren ötiroid hastalarda desfluran ve propofolün tiroid hormonu salınımı üzerine etkilerinin karşılaştırılmasıdır.Yöntemler: Tek seviye lomber diskektomi geçiren American Society of Anesthesiology (ASA) I-II, 21-65 yaş arası, ötiroid 40 hasta çalışmaya dahil edildi. Hastalar randomize olarak 2 farklı gruba (n=20) ayrıldı. Anestezi idamesinde Grup D desfluran inhalasyon ajanı ve remifentanil IV infüzyonu aldı. Grup P ise IV propofol ve remifenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In this study, patients with propofol anesthesia showed higher serum T4 levels at 3 months post‐operatively, compared to patients with sevoflurane anesthesia, and there was a significant group‐by‐time interaction. In contrast, previous clinical studies of patients undergoing lumbar discectomy or gynecological laparoscopy showed that serum‐free T4 levels did not differ at 4 or 24 hours post‐operatively between patients anesthetized with sevoflurane or desflurane and those anesthetized with propofol 10,20 . This discrepancy was presumably due to the effects of other confounders (i.e., pre‐operative thyroid function status, including serum‐free T4 level and the number of patients with TSH deficiency), rather than the effects of anesthetics.…”
Section: Discussionmentioning
confidence: 65%
“…In this study, patients with propofol anesthesia showed higher serum T4 levels at 3 months post‐operatively, compared to patients with sevoflurane anesthesia, and there was a significant group‐by‐time interaction. In contrast, previous clinical studies of patients undergoing lumbar discectomy or gynecological laparoscopy showed that serum‐free T4 levels did not differ at 4 or 24 hours post‐operatively between patients anesthetized with sevoflurane or desflurane and those anesthetized with propofol 10,20 . This discrepancy was presumably due to the effects of other confounders (i.e., pre‐operative thyroid function status, including serum‐free T4 level and the number of patients with TSH deficiency), rather than the effects of anesthetics.…”
Section: Discussionmentioning
confidence: 65%
“…Although taking into consideration the different conditions of exposures and the remarkable inter-subject variability, the thyroid is very sensitive to the action of chemical disruptors [43]. Therefore, it cannot be ruled out that physicians, e.g., anesthesiologists and surgeons, employees in rubber and ceramic industry, as well as those involved in the packaging units of a pharmaceutical industry, may be exposed to chemicals, e.g., anesthetics, metals and plasticizers that may mediate hormonal alterations as reported in occupational, epidemiological and experimental settings [44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…A study compared the impact of desflurane and propofol on thyroid hormone levels in euthyroid patients. There was no significant difference in the release of TSH, FT3 and FT4 between the two anesthetics [21]. Consequently, which anesthetic induces a more intensive impact on the pituitary thyroid axis should be researched further.…”
Section: Plos Onementioning
confidence: 91%